Maternal tetanus, diphtheria, and acellular pertussis (Tdap) and influenza immunization: an overview. (18th October 2021) - Brillo, Eleonora; Tosto, Valentina; Giardina, Irene; Buonomo, Ersilia
Abstract: Background: Maternal tetanus, diphtheria, and acellular pertussis (Tdap) and influenza immunization for women during pregnancy (the so-called "maternal immunization") has been introduced in several countries, and recently also in Italy, to protect mother and fetus during pregnancy, infant in his first months of life and mother during postpartum period. However, very low vaccination coverage rates have been reached due to several variables. Methods: A literature search was conducted on PubMed and Embase, including any experimental or observational studies, to assesses existing evidence on the effectiveness, efficacy, safety and optimal timing of administration of Tdap and influenza immunization in pregnancy for mothers and their infants. The search was finalized in August 2019. Results: Reviewing the literature, we identified only a few studies that, among several maternal and infant outcomes, found sporadic significant associations with maternal influenza immunization and even less with Tdap immunization. Moreover, most of the authors of these studies explained these findings as a result of residual confounding effect. The effectiveness of maternal influenza immunization is more complicated to prove than the effectiveness of Tdap immunization because of several reasons. Not all nations recommend and offer vaccines in the same weeks of pregnancy and this one manifests the complexity in defining the best timing for Tdap or influenza immunization. Conclusions: The safety of maternal Tdap or influenza immunization is supported by the evidence so far, however, regular surveillance should be maintained, especially with regard to the influenza vaccine that changes in formulation each year. There is a need to optimize the timing of vaccination in pregnancy and to have a national system of detection of maternal immunization in each country.